2019
DOI: 10.1186/s12944-019-1008-5
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cruciate ligament transection alters the n-3/n-6 fatty acid balance in the lapine infrapatellar fat pad

Abstract: BackgroundThe infrapatellar fat pad (IFP) of the knee joint has received lots of attention recently due to its emerging role in the pathogenesis of osteoarthritis (OA), where it displays an inflammatory phenotype. The aim of the present study was to examine the infrapatellar fatty acid (FA) composition in a rabbit (Oryctolagus cuniculus) model of early OA created by anterior cruciate ligament transection (ACLT).MethodsOA was induced randomly in the left or right knee joint of skeletally mature New Zealand Whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 40 publications
1
16
0
1
Order By: Relevance
“…Neither were the FA proportions in SF and IFP directly interrelated in human subjects [ 50 ]. Elevated IFP proportions of 20:4n-6 and 22:6n-3 together with lowered total MUFA percentages and n-3/n-6 PUFA ratios in a rabbit model of early OA [ 95 ] partly confirmed the secretion data from humans [ 93 ]. Van de Vyver et al [ 55 ] suggested that inflammation could be less pronounced in the IFP of end-stage OA and this may be associated with the reduced n-6 PUFA levels in SF.…”
Section: Osteoarthritismentioning
confidence: 66%
“…Neither were the FA proportions in SF and IFP directly interrelated in human subjects [ 50 ]. Elevated IFP proportions of 20:4n-6 and 22:6n-3 together with lowered total MUFA percentages and n-3/n-6 PUFA ratios in a rabbit model of early OA [ 95 ] partly confirmed the secretion data from humans [ 93 ]. Van de Vyver et al [ 55 ] suggested that inflammation could be less pronounced in the IFP of end-stage OA and this may be associated with the reduced n-6 PUFA levels in SF.…”
Section: Osteoarthritismentioning
confidence: 66%
“…A high n-6/n-3 PUFA ratio in the diet and in the body is associated with obesity and several other pathological conditions [13, 14]. Our research group observed an increase in the IFP n-6/n-3 PUFA ratio due to experimentally induced early OA in a rabbit model [42] and, in human plasma, a high n-6/n-3 PUFA ratio was associated with greater pain and functional limitations of the OA knee [43], suggesting implications in joint diseases. However, there was no relationship between SF n-3/n-6 PUFA ratios and OA severity or synovitis in an obese mouse model of OA [44].…”
Section: Discussionmentioning
confidence: 99%
“…Each knee was dissected and divided into six anatomical regions: lateral and medial femoral condyle, lateral and medial tibial plateau, femoral groove, and patella ( n = 96, Table 1 ). Details on animal housing, husbandry conditions, and diet are described in a previous study (Mustonen et al, 2019 ). All experiments were carried out under the guidelines of the Canadian Council on Animal Care and were approved by the committee on Animal Ethics at the University of Calgary (Renewal 3 for ACC Study #AC11­0035).…”
Section: Methodsmentioning
confidence: 99%